Investigating the protective capacity of polymethylsiloxane polyhydrate against chromium (VI)-induced neurotoxicity of the rat optic nerve (Ukrainian Journal of Ophthalmology, 2025)
Background: Toxic optic neuropathy commonly develops in the presence of exogenous factors. With progression of the process, acute or chronic progressive death of retinal ganglion cells and their axons develops, leading to partial or total optic atrophy with visual function loss. Investigation of the effect of chromium (VI) on the optic nerve and evaluation of potential pathogenetic treatments of this effect are deemed relevant because of the global environmental crisis associated with pollution from chromium.Purpose: To examine chromium (VI)-induced morphological changes in the rat optic nerve and to experimentally assess the efficacy of polymethylsiloxane polyhydrate (PMSPH) for correction of induced changes.Material and Methods: Seventy two white outbred adult male rats were distributed in three groups (24 animals each) given water ad libitum. Animals in group 1 (a control group) were intact and given normal drinking water. Those in group 2 were given chromium (VI) (K2Cr2O7)-enriched (0.02 mol/L) drinking water but not Enterosgel. Animals in group 3 were given K2Cr2O7-enriched (0.02 mol/L) drinking water and treated with oral Enterosgel (0.8 mg/kg). Animals were decapitated under ether anesthesia and the intracranial optic nerve was harvested at three time points (20, 40 and 60 days after initiation of the experiment), and changes in the optic nerve were assessed by histomorphology and electron microscopy.Results: Histomorphology found disrupted and fragmented nerve fibers, edematous connective tissue septa, and diffuse cellular gliosis in day-60 intracranial optic nerve specimens obtained from animals given chromium (VI)-enriched drinking water and not treated with Enterosgel. In addition, there was scanning electron microscopy evidence of electrolyte disbalance and accumulation of chromium (VI). Treatment with Enterosgel completely inhibited the effect of chromium (VI) on the rat optic nerve at days 20 and 40, and we observed only minimal consequences of discirculatory changes in day-60 specimens obtained from animals given chromium (VI)-enriched drinking water and treated with Enterosgel.
Keywords: chromium (VI); experiment; toxicity; optic nerve; Enterosgel; scanning electron microscope